The Urgency of Applying Article 39 paragraph (2) UUJN Against Prevention of Indications of Criminal Acts in Notary Deeds - Prayitno, Urip; Saleh, Moh. (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2023)
Notaries are authorized to make authentic deeds (Article 15 paragraph (1) of Law Number 2 of 2014 concerning the Position of Notary). A notary has the potential to be entangled in criminal law, if it is proven that intentionally or unintentionally the Notary together with the parties / interceptors to make a deed with the intention and purpose of benefiting one party and harming the other party. This study aims to examine the urgency of applying Article 39 paragraph (2) of the UUJN to the prevention of indications of criminal acts in notarial deeds. The research method used is the normative juridical method, which is carried out by analytical descriptive analysis. The results of the study concluded that notaries cannot be held liable when the element of fraud and mistakes is committed by the confronters, because the Notary only records what is submitted by the parties to be poured into the deed (partij deed). False statements submitted by the parties are the responsibility of the parties. With regard to the actions of notaries who commit criminal acts of forgery of deeds or criminal acts of false information committed by the parties, UUJN does not specifically regulate related to criminal provisions because it is based on the principle of legality which is the principles in the Criminal Code.